2020
DOI: 10.1088/1361-6501/ab6eca
|View full text |Cite
|
Sign up to set email alerts
|

Damage localization in cross-ply laminated composite plates under varying temperature conditions using Lamb waves

Abstract: Lamb wave-methods are reported to be very effective in detecting and localizing defects in thin plate structures. However, the accuracy of damage detection using Lamb waves is affected significantly by variations of environmental and operating conditions. In the present study, an improved methodology is presented to calculate the damage residue measure from current state responses that compensates the effect of operational and environmental changes. The proposed damage residue is obtained by comparing the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…The fiber Bragg grating (FBG) sensors [18] can easily form a network without causing damage to the composite plate structures. And the FBG sensors have the advantages of small sizes, high flexibility, sensitivity, and anti-electromagnetic interference ability [19,20]. So the FBG sensors are widely used in many fields of SHM, such as damage detection of highway bridges and impact localization of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…The fiber Bragg grating (FBG) sensors [18] can easily form a network without causing damage to the composite plate structures. And the FBG sensors have the advantages of small sizes, high flexibility, sensitivity, and anti-electromagnetic interference ability [19,20]. So the FBG sensors are widely used in many fields of SHM, such as damage detection of highway bridges and impact localization of composite materials.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Most of the reported literature is related to identifying and localising damage using the narrowband excitation signal. [12][13][14][15][16][17][18][19][20] The sensitivity of the narrowband excitation signal to the damage width depends on the excitation signal's centre frequency. Lowe et al 21 found that the reflection coefficient from the damage site exhibited a cosinusoidal periodic shape with a notch width.…”
Section: Introductionmentioning
confidence: 99%
“…The isolated signals are regarded as a specific signature to indicate the presence of structural damage. However, reliable baseline data are extremely difficult and impractical to obtain in realistic conditions due to varying environmental and operational conditions, such as fluctuations in temperature [ 14 , 15 ], variation in surface moisture [ 16 , 17 ], vibrations, loading conditions [ 18 , 19 , 20 ], and so forth. As a result, the baseline-dependent method can identify damages that are sometimes mistaken in the presence of these varying conditions.…”
Section: Introductionmentioning
confidence: 99%